Dissolved gaseous Hg (DGM) in the Mediterranean surface and deep waters - Kotnik J.; Horvat M. (E3S Web of Conferences, 2013)
Dissolved gaseous mercury (DGM) was studied in surface and deep waters of the Mediterranean Sea for last 12 years during several oceanographic cruises on board the Italian research vessel Urania and covered both Western and Eastern Mediterranean Basins as well as Adriatic Sea. DGM was measured together with other mercury species (RHg - reactive Hg, THg - total Hg, MeHg - monomethyl Hg and DMeHg - dimethylmercury), and with some water quality parameters in coastal and open sea deep water profiles, however only DGM will be discussed here. DGM represents a considerable portion of THg (average of about 20 %) in Mediterranean waters. Spatial and seasonal variations of measured DGM concentrations were observed in different indentified water masses as well as iwere observed. DGM was the highest in the northern Adriatic, most polluted part of the Mediterranean Sea as the consequence of Hg mining in Idrija and heavy industry of northern Italy.Generally, average DGM concentration was higher in W and E Mediteranean Deep Waters (WMDW and EMDW) and Leavantine Intermediate Water (LIW) than overlaying Modified Atlantic Water (MAW), however it was the highest in N Adriatic Surface waters and consequently in out flowing Adriatic Deep Waters (ADW). In deep water profiles the portion of DGM typically increased at depths with oxygen minimum and then towards the bottom, especially in areas with strong tectonic activity (Alboran Sea, Strait of Sicily, Tyrrhenian Sea), indicating its bacterial and/or geotectonic origin. A comparison of the results obtained in this study to others performed in the Mediterranean shows no significant differences. Results were also compared to the results obtained in the Pacific and Atlantic Oceans. During last oceanographic cruise in 2011 covering area between Livorno and Lipari Islands a novel method for continuous DGM determination in surface waters (Wangberg and Gardfeldt, 2011) was applied and compared to standard method.